Stunting and Its Implications on Cognitive Ability and Language Development - Roy Romey Daulas Mangunsong (Masters Program in Public Health, 2025)
Background: Stunting, a chronic nutritional disorder from prolonged inadequate intake, affects not only physical growth but also cognitive and language development. Mid-upper arm circumference (MUAC) and maternal education are important predictors of stunting risk. Guided by early childhood development theory, this study aims to analyze the implications of stunting on children's cognitive abilities and language development in Karanganyar Regency to inform effective intervention strategies.Subjects and Method: This was a cross-sectional study conducted in Karanganyar Regency, Central Java, from April to August 2024. A total of 112 children were selected through purposive sampling. The independent variables were stunting status, cognitive ability, mid-upper arm circumference, and maternal education, while the dependent variable was language development. Data were collected through standardized measurements and structured interviews. Logistic regression analysis was performed using Stata 13 to examine the associations between variables.Results: Bivariate analysis revealed that delayed language development was significantly associated with stunting (OR=19.05; p<0.001), poor cognitive ability (OR=18.63; p<0.001), MUAC <13 cm (OR=9.41; p<0.001), and low maternal education (OR=21.21; p<0.001). Multivariate analysis showed that stunting (b=2.09; 95% CI=1.02 to 3.16; p<0.001) and poor cognitive ability (b=2.06; 95% CI=0.99 to 3.13; p<0.001) had direct effects on delayed language development.Conclusion: Stunting directly impairs children's cognitive ability and language development. Additionally, maternal education and mid-upper arm circumference have indirect effects on these outcomes through their influence on stunting. These findings highlight the need for integrated nutritional and educational interventions to promote optimal child development.